Limitations and Barriers of Dentists to Dental Care for People with Intellectual Disability in Thailand - บุรพลกุล, ภัตติมา (Thai Dental Public Health Journal, 2008)
Objectives : The objective of this study was to examine limitations and barriers of dentists to provide dental services for people with intellectual disability in Thailand. Methods: A cross-sectional survey was obtained by sending a postal questionnaire to dentists in Thai Pediatric Dental Association to assess their perception about limitations and barriers to provide dental care for people with intellectual disability and suggest how to improve accessibility. The data were analyzed using frequencies and percentages. Results : Most respondents had experiences in dental service for the intellectual disabilities and generally agreed that they were responsible for the roles of dental care including oral health prevention and promotion, dental treatment and also role of system development. Their perception about limitations and barriers were difficulties in communication and behavioral management, lack of skill, lack of workplace facilities, lack of consulting and referral system, and also lack of policy. Recommendations to improve accessibility to dental services were promoting network and referral system, skill training for dentists and other personnel, policy and motivations for dentists to provide dental care and contracting units of dental services for the intellectual disabilities. These findings could be considered to improve accessibility to dental care of people with intellectual disability in Thailand in the future.